The Effect of Financial Distress and Capital Structure Moderated by Company Size - Erawati, Teguh; Pratiwi, Cindy; Grediani, Evi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Financial distress is a condition where the company’s finances are in unhealty or crisis and occurs before bankruptcy which is caused because the company does not always run in accordancee with the rules and regulations chaused because the company does not always run according to the plan. The purpose of this study is to examine the effect of profitability ratios and capital structure on the likelihood of financial distress in companies, as well as how company size moderates this relationship, with the aim of providing practical and theoretical insights for corporate financial management and helping investors to make better investment decisions. The sample used in the research is all manufacturing companies listed on the IDX in 2018-2021. The number of data 220 companies. The research method used is using the documentation method, namely data obtained from financial reports and annual reports of manufacturing companies listed on the IDX during the 2018-2021 research period. The data analysis technique uses descriptive statistical tests, classical assumption tests, and hypothesis testing in the form of multiple linear regression tests, F tests, R2 tests and MRA tests. The significance level used in determining the research results is 0.05. The results of this research show that the profitability ratio does not have a significant effect on financial distress. Capital structure has a positive and significant effect on financial distress. This means that the higher the company's debt level, the more it can cause financial distress. Company size is able to moderate and significantly influence profitability on financial distress. Company size is not able to significantly moderate the influence of capital structure on financial distress.